The Effects of Executive and Company Characteristics on Tax Aggressiveness - Dewi, Kristina Surya; Yasa, Gerianta Wirawan (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020)DO - 10.24843/JIAB.2020.v15.i02.p10, 2020)
Tax aggressiveness is the act of manipulating profits carried out through tax planning that can be both legal and illegal. Based on the agency theory, the different interests of agents and principals may become a source of conflict. The aim of this study is to determine and obtain empirical evidence on the effect of executive characteristics, profitability, leverage, capital intensity, and company size on tax aggressiveness. This research was conducted on manufacturing companies listed on Indonesia Stock Exchange in 2016-2018, because the Indonesian economy has started to recover since 2016 and continued until 2018, so it will have an impact on tax revenues. The sample was selected using purposive sampling technique and obtained 70 manufacturing companies. Data analysis technique used is multiple linear regression analysis. The results show that executive characteristics, profitability, and company size had a positive effect. While leverage and capital intensity had negative effect on tax aggressiveness. Keywords:  Tax aggressiveness, executive characteristics, profitability, leverage, capital intensity, company size.